The Role of Machiavellianism on Counterproductive Work Behavior in Student Organizations Islamic Economic Perspective - Hidayatulloh, Agung; Nuzulia, Siti (ITB AAS INDONESIA Surakarta, 2024)
This research is a type of quantitative research with a cross-sectional study design. The aim of this research is to analyze the influence of Machiavellianism on counterproductive work behavior in student organizations. Research data was obtained through questionnaire answers given to a research sample of 211 respondents which was then confirmed again through other significant data. Data analysis uses linear regression analysis test techniques. The research results show that Machiavellianism has a positive influence on counterproductive work behavior. Machiavellianism influences counterproductive work behavior with level of p=.000 (